Early Preterm meconium stained amniotic fluid is an independent risk factor for peripartum maternal bacteremia. (March 2021) - Attali, Emmanuel; Kern, Guy; Reicher, Lee; Fouks, Yuval; Gamzu, Ronni; Yogev, Yariv; Many, Ariel
Abstract: Objective: To investigate the association of maternal peripartum bacteremia and meconium stained amniotic fluid in early preterm deliveries. Methods: We conducted a single center retrospective study, in a tertiary university affiliated medical center. The study cohort included women with culture proven maternal bacteremia who had a preterm delivery between 24–34 weeks of gestation. The control group composed of women with similar gestational age at delivery without bacteremia. Maternal characteristics were compared between the groups. Results: During the six-years study period there were 86, 590 deliveries in our center. 2625 (3.03 %) women had early preterm deliveries (24–34 weeks), of them 22 (0.84 %) were diagnosed with peripartum bacteremia. The groups were similar with regard to obstetric and demographic characteristics. In the peripartum maternal bacteremia group, we found significantly higher rates of MSAF (6.86 % vs 22.73 %, p = 0.036). Logistic regression of multivariable analysis demonstrated that MSAF is an independent risk factor for maternal bacteremia adjusted for gestational age, intrapartum fever and leukocytosis (Odd Ratio 4.29, 95 % CI 1.26–12.56, p = 0.012) Conclusion: Preterm MSAF is an independent risk factor for maternal bacteremia among women with early preterm delivery. More studies are needed to determine the need for broad spectrum antibiotic prophylaxis therapy in preterm deliveries complicated by MSAF.